CD11c/CD18 expression is upregulated on blood monocytes during hypertriglyceridemia and enhances adhesion to VCAM-1 - Gower, R. Michael (2010)
OBJECTIVE: Atherosclerosis is associated with monocyte adhesion to the arterial wall that involves integrin activation and emigration across inflamed endothelium. Involvement of β2-integrin CD11c/CD18 in atherogenesis was recently shown in dyslipidemic mice, which motivates our study of its inflammatory function during hypertriglyceridemia in humans. METHODS AND RESULTS: Flow cytometry of blood from healthy subjects fed a standardized high fat meal revealed that at 3.5 hours postprandial, monocyte CD11c surface expression was elevated and the extent of upregulation correlated with blood triglycerides. Monocytes from postprandial blood exhibited an increased light scatter profile, which correlated with elevated CD11c expression and uptake of lipid particles. Purified monocytes internalized triglyceride-rich lipoproteins isolated from postprandial blood through LRP-1, and this also elicited CD11c upregulation. Lab-on-a-chip analysis of whole blood showed that monocyte arrest on a VCAM-1 substrate under shear flow was elevated at 3.5 hours and correlated with blood triglyceride and CD11c expression. At 7 hours postprandial, blood triglycerides decreased and monocyte CD11c expression and arrest on VCAM-1 returned to fasting levels. CONCLUSIONS: During hypertriglyceridemia, monocytes internalize lipid, upregulate CD11c, and increase adhesion to VCAM-1. These data suggest that analysis of monocyte inflammation may provide additional framework for evaluating individual susceptibility to cardiovascular disease.